Integrating Sharia Economic Law and the Green Economy in Nature-Based Ecotourism for Local Community Development - Hidayat Darussalam; Yosy Arisandy; Dmytro Dronik; Nataliia Bilak; Volodymyr Shalimov (Nusantara: Journal of Law Studies, 2026)
This article aims to integrate the principles of Islamic economics and law with the green economy to manage nature-based ecotourism in Bengkulu Province, thereby generating economic benefits for surrounding communities while remaining within the framework of environmental conservation. The exploitative nature of nature-based tourism management in Bengkulu Province is evident in the utilization of protected forest and coastal areas, which often disregards the unique ecosystem capacity of Sumatra. The development of supporting infrastructure at strategic points, such as mountainous areas or coastal edges, is often carried out without in-depth environmental studies, leading to the degradation of native vegetation and increasing the risk of ecological disasters, such as landslides and abrasion. This study employs a qualitative case study approach to explore the integration of Sharia economic principles and the green economy within the development of ecotourism in Bengkulu Province. Data were gathered through in-depth interviews, field observations, and documentation involving relevant stakeholders. The findings demonstrate that this integration is firmly implemented in economic sustainability by allocating tourism profits to Islamic social finance instruments (Zakat, Infaq, and Alms/ZIS), which are managed transparently for village infrastructure development. Furthermore, the practical application of the green economy is manifested through the construction of eco-friendly facilities and integrated waste management systems that protect the biodiversity of the tropical rainforest, a unique identity of Bengkulu. Academically, this research contributes to the literature by bridging the gap between Sharia economic law and sustainability studies, particularly by positioning Maqāṣid al-Sharīʿah as a normative foundation for environmental governance in ecotourism. It also enriches the discourse on Islamic social finance by demonstrating its practical role in supporting community-based development within a green economy paradigm.